2019
DOI: 10.1002/imhj.21753
|View full text |Cite
|
Sign up to set email alerts
|

The early biopsychosocial development of boys and the origins of violence in males

Abstract: We apply a biopsychosocial approach to introduce early‐in‐life experiences that explain a significant part of the male preponderance in the perpetration of violence. Early caregiver abuse and neglect, father absence, and exposure to family and neighborhood violence exacerbate boys’ greater risk for aggressive behavior and increase the probability of carrying out violent acts later in life. We examine the development of the psychological self and explore conditions that encourage physical aggression, focusing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
5
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 130 publications
1
5
0
3
Order By: Relevance
“…Second, it is also widely recognized that the very large majority of serious violence in society is perpetrated by males. Third, there is a long‐standing perspective recognizing that the male brain is more vulnerable to early adverse influences that disturb the normal development of the brain (Golding & Fitzgerald, this issue), thus placing the male brain more at risk for a wide variety of disorders (Schore, ). Taking these positions together, it is reasonable to hypothesize that early prenatal and postnatal health influences may particularly place males at risk for aggressive and violent behavior by influencing brain and neurobiological processes.…”
mentioning
confidence: 99%
“…Second, it is also widely recognized that the very large majority of serious violence in society is perpetrated by males. Third, there is a long‐standing perspective recognizing that the male brain is more vulnerable to early adverse influences that disturb the normal development of the brain (Golding & Fitzgerald, this issue), thus placing the male brain more at risk for a wide variety of disorders (Schore, ). Taking these positions together, it is reasonable to hypothesize that early prenatal and postnatal health influences may particularly place males at risk for aggressive and violent behavior by influencing brain and neurobiological processes.…”
mentioning
confidence: 99%
“…Hollway (2006) has suggested that the capacity to care develops within early dyadic and triadic family relationships. The men in the present sample described childhood memories of unsafe triangulation due to violence or paternal absence, which according to neurodevelopmental theory heightens the risk for developing problems with affect-regulation, violence perpetration, and parenting (Beaver and Belsky 2011;Belsky and Beaver 2011;Golding and Fitzgerald 2019). They reported few and unstable experiences of male sensitive care, which according to gender-oriented psychologists (Levant 2005) may provide limited capacity to care for others later in life.…”
Section: Discussionmentioning
confidence: 77%
“…In line with this, men's use of intimate partner violence has been associated with aggressive biases in socialinformation processing (Setchell et al 2017). Social information processing that heightens the risk for interpersonal violence has, amongst others, been associated with early trauma and stress during critical neurodevelopmental periods (Golding and Fitzgerald 2019;Murphy 2013). Genetic susceptibility for being impacted by environmental stress early in life has been found to be negatively associated with men's emotion regulation in adolescence (Belsky and Beaver 2011) and parental functioning in early adulthood (Beaver and Belsky 2011).…”
mentioning
confidence: 88%
“…Si investigaciones como esta ponen de relieve la importancia de la "gura paterna en la vida de un niño o niña, entonces vale la pena re%exionar sobre estrategias que ayuden a promover el vínculo paterno-"lial, más aún cuando se ha sugerido que la ausencia del padre en la niñez y en la adolescencia podría constituir un factor de riesgo para comportamientos violentos y sociopáticos en la vida adulta (Golding & Fitzgerald, 2019). Se ha propuesto que los juegos agresivos, aspecto característico del comportamiento paterno y de la relación del padre con su hijo e hija, le permite a este combinar de forma creativa el amor y la agresividad (Rodica, 2019).…”
Section: Discussionunclassified